The effectiveness of video and deck card use in crafting the skills of writing experience within the elementary school students - Wulan Ambarwati; C Asri Budiningsih (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2018)
The aims of this research are to find out (1) the differences of the use of video and random cards with pictures and worksheets on the skill of writing experience-story of fifth grade students of SD Negeri Panggang; (2) the effectiveness of the use of video and random cards compared to the pictures and worksheets on the skill of writing experience-story of fifth grade students of SD Negeri Panggang.The research approach is quantitative and the method is quasi-experimental with pretest and posttest. Based on the results of the calculation of the t-test, the score of posttest on the experimental group and the control group is 2.193 with df=38 obtained p=0.035 which are less than 5% (p 0.05). The t-test results showed that there was the difference between the skills of writing experience-story from the experimental group that uses video and random cards with pictures and worksheets. Gain score showed the differences in the level of per cent (t = 2.895; P 0.05) (t = 2.895; 0.006 0.05). The results showed that video has more effective effects than random cards with pictures and worksheets on improving the skills of writing experience story of fifth-grade students of SD Negeri Panggang.